PERBANDINGAN REAKSI PASAR SEBELUM DAN SESUDAH PENGUMUMAN OPINI AUDIT UNQUALIFIED - Angga Wahyu Prasetyo; Rini Rini (MIX: JURNAL ILMIAH MANAJEMEN, 2014)
Abstract: This study aims to determine the difference of market reaction before and after the announcement of unqualified audit opinion (WTP) on the companies that included in the index LQ 45 period of 2012-2014. This study was performed on 66 samples that announced WTP audit opinion on the annual financial statements for the years ended 2011-2013. The statistical method used is T-test Paired Samples (t-test) with event period for 15 days, namely is 7 trading days before until 7 days after the announcement of WTP audit opinion. The results of this study showed that there was no significant difference of market reaction seen from Average Abnormal Return before and after the announcement of WTP audit report (Unqualified Audit Report). This was showed from the results of Paired Samples Test, with the number of t-test results is -1.502 and a significance value of 0.138, or in other word the significance value is > á ( 0.138 > 0.05 ), this mean rejecting Ha. Based on the results of this hypothesis testing can be concluded that investors reacted negatively upon the announcement of WTP audit report conducted by the companies whose the shares listed in LQ 45 Index period of 2012-2014. This result indicated that the information of unqualified audit opinion report (WTP) was not used by the investors as one of reference in taking investment decisions.Keywords: Market Reaction , Unqualified Audit Opinion , Average Abnormal Return